A culture-dependent and metagenomic approach of household drinking water from the source to point of use in a developing country. (1st February 2019) - Bae, Sungwoo; Lyons, Colleen; Onstad, Nora
Abstract: Rural households in developing countries rely on communal water supplies and household water frequently becomes contaminated following its collection, transportation and during its storage. Using culture-dependent and -independent techniques, we examined the changes in microbial water quality between communal tap water and household water storage in a rural area of Cameroon, Africa. The culturable fecal indicator bacteria (FIB) were used to assess the potential health risks associated with different household water storage conditions (e.g., type of container and open vs. closed container) and interventions (e.g., water storage days, cleaned on the last day of use, and hygiene practices). Only the amount of days the water was stored significantly differed (p-value < 0.05), which showed that potential health risks increased when water was stored for more than 3 days. The higher abundance of molecular FIB in biofilm than household water suggested that omnipresent biofilm in household water could potential health risk. The high-throughput sequencing revealed that the most abundant phylum was Proteobacteria, followed by Actinobacteria and Bacteroidetes in both the water and the biofilm samples. Bacterial genera seen in biofilm bacteria, such as Pseudomonas, Acinetobacter and Comamonas . Acinetobacter, Chryseobacterium, Stenotrophomonas and Corynebacterium, were relatively more abundant in the biofilm than in the water. Potential bacterial pathogens including Acinetobacter baumannii, Citrobacter freundii, Stenotrophomonas maltophilia and Haemophilus influenza, were detected in household water and biofilm. The microbial quality might be affected by water-storage time and households repeatedly using the same water storage containers without proper sanitization, triggering microbial regrowth and biofilm formation on water containers. Higher bacterial diversity and potentially pathogenic bacteria found in the biofilm samples of a household water supply are unhealthy for the house's inhabitants. It is important to develop interventions aimed at preventing the formation of these dangerous biofilms in a communal water supply. Graphical abstract: Image 1 Highlights: Using culture-dependent and -independent techniques, microbial water qualities was examined. Potential health risks increased when water was stored for more than 3 days. Higher bacterial diversity and potentially pathogenic bacteria found in the biofilm samples. Poor sanitation and poor hygiene trigger microbial regrowth and biofilm formation.